prohibiting through command and commanding through prohibition (the study of speech act in javanese culture) - pramudyawardhani, s. r. (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2017)
This study of speech act discusses a socio-pragmatic phenomena found in Javanese daily communication that, in prohibiting, Javanese people prefer command to prohibition, and in commanding, they prefer prohibition to command. This is due to the fact that in Javanese peopleâs view, command is the most effective strategy to prohibit someone to do something and prohibition is the most effective strategy to command someone to do something. There are 20 samples of Javanese utterances which are analyzed here. The analysis covers Locution, Illocution, and Perlocution of each sample. However, the effectiveness of those strategies is influenced by two social factors, namely age and social class. Those strategies are effective if they are used by the elder people to the younger ones and by the higher social class to the lower one, but not vice versa.